Analisis Antropometrik Dan VO2 Max Dengan Prestasi Pemain BKMF Tenis Meja FIK UNM - Sahabuddin, Sahabuddin (UNIVERSITAS NEGERI MAKASSSAR, 2019)
ABSTRACTThe research objective was to determine the effect of anthropometrics and VO2 max on the performance of table tennis players. The research design or type of research used in this study is correlational. The population in this study were all BKMF FIK UNM table tennis players. The sample in this study were players. The data analysis used was univariate analysis and bivariate analysis. By using the Chi – Square statistical test with a significance level of α = 0.05. Based on the results of data analysis, it can be concluded that; (1) There is a significant anthropometric difference with the achievement of table tennis athletes at BKMF Tennis table FIK UNM. This is evidenced by the results of data processing through the One Way Anova test, the average value of each group at anthropometric <0.05 means that Ho is rejected, meaning that there is a significant difference between groups, (2) There is a significant difference between VO2 Max and the performance of table tennis athletes at BKMF Tenismeja. FIK UNM. This is proven by the results of data processing through the One Way Anova test, the average value of each group at VO2 Max <0.05 means that Ho is rejected, meaning that there is a significant difference between groups, and (3) There is a significant difference in the frequency of training with the achievement of table tennis athletes unit of tensimeja Unhas. This is proven by the results of data processing through the One Way Anova test, the average value of each group at training frequency <0.05 means that Ho is rejected, meaning that there is a real difference between groups. ABSTRAKTujuan Penelitian adalah untuk mengetahui pengaruh antropometrik dan VO2 max dengan prestasi pemain tenismejaDesain penelitian atau jenis penelitian yang digunakan dalam penelitian ini adalah korelasional. Populasi dalam penelitian ini adalah seluruh pemain tenismeja BKMF FIK UNM. Sampel dalam penelitian ini adalah pemain. Analisis data yang digunakan adalah analisa univariate dan analisa bivariate. Dengan menggunakan uji statistic Chi – Square dengan tingkat kemaknaan α = 0,05. Berdasarkan hasil analisis data dapat disimpulkan bahwa; (1) Ada perbedaan yang signifikan antropometrik dengan prestasi atlet tenismeja pada BKMF Tenismeja FIK UNM. Hal ini terbukti dengan hasil pengolahan data melalui Uji One Way Anova diperoleh nilai rata-rata tiap kelompok pada antropometrik < 0.05 berarti Ho ditolak, berarti ada perbedaan nyata antara kelompok, (2) Ada perbedaan yang signifikan VO2 Max dengan prestasi atlet tenismeja pada BKMF Tenismeja FIK UNM. Hal ini terbukti dengan hasil pengolahan data melalui Uji One Way Anova diperoleh nilai rata-rata tiap kelompok pada VO2 Max < 0.05 berarti Ho ditolak, berarti ada perbedaan nyata antara kelompok, dan (3) Ada perbedaan yang signifikan frekuensi latihan dengan prestasi atlet tenismeja pada unit tensimeja Unhas. Hal ini terbukti dengan hasil pengolahan data melalui Uji One Way Anova diperoleh nilai rata-rata tiap kelompok pada frekuensi latihan < 0.05 berarti Ho ditolak, berarti ada perbedaan nyata antara kelompok.